Pengenalan dan Kesiapan Teknologi 5G SLB Negri Labuha, Kab. Halmahera Selatan, Maluku Utara: Introduction and Readiness of 5G Technology SLB Negri Labuha, Kab. South Halmahera, North Maluku - Saiful Do. Abdullah; Syarifuddin Kapita; Achmad Fuad; Adelina ibrahim (Jurnal Suara Pengabdian 45, 2022)
The development of telecommunications technology has grown very rapidly. This is in line with the extraordinary increase in internet data traffic. The use of the internet has been used in all layers of the age segment, both the older generation to the younger generation. Global competition in the future is very tight and knowledge of technology, especially telecommunications technology, is needed. 5G technology stands for 5th Generation which refers to the fifth generation of mobile phones. 5G technology has incredible data capabilities and has the ability to unify unlimited call volume and unlimited data broadcasts in the latest mobile operating systems. Currently, Indonesia is lagging behind in the application of 5G technology. Indonesia is currently still preparing regulations and the frequency spectrum used in the implementation of 5G technology. Therefore, the socialization of the Introduction and Readiness of 5G Technology SLB Negri Labuha, Kab. South Halmahera, North Maluku.